Basal Mild Dehydration Increase Salivary Cortisol After a Friendly Match in Young Elite Soccer Players - Castro-Sepulveda, Mauricio; Ramirez-Campillo, Rodrigo; Abad-Colil, Felipe; Monje, Camila; Peñailillo, Luis; Cancino, Jorge; Zbinden-Foncea, Hermann (Frontiers in Physiology, 2018)
A soccer match induce changes in physiological stress biomarkers as testosterone (T), cortisol (C), and testosterone:cortisol (T:C) ration. Hydration state may also modulate these hormones, and therefore may alter the anabolic/catabolic balance in response to soccer match. The role of hydration status before the match in this biomarkers has not yet been reported. The aim of this study was to compare the salivary T, C, and the T:C ratio responses after two friendly matches in well-hydrated and mild-dehydrated (MD) elite young male soccer player. Seventeen players (age, 16.8 ± 0.4 years; VO2max 57.2 ± 3.6 ml/kg−1/min−1) were divided into two teams. Before the matches the athletes were assessed for hydration level by the urine specific gravity method and divided for the analysis into well-hydrated (WH; n = 9; USG < 1.010 g/mL−1) and mild-dehydrated (MD; n = 8; USG 1.010 to 1.020 g/mL−1) groups. Hormones were collected before and after each match by saliva samples. The mean (HRmean) and maximal (HRmax) heart rate were measured throughout the matches. A two-way ANOVA was used to compare T, C, and T:C between and within groups. Similar HRmean (WH, 83.1 ± 4.7%; MD, 87.0 ± 4.1; p = 0.12) and HRmax (WH, 93.2 ± 4.4%; MD, 94.7 ± 3.7%; p = 0.52) were found for both groups during the matches. No differences were found before the matches in the T (p = 0.38), C (p = 66), nor T:C (p = 0.38) between groups. No changes within groups were found after matches in neither group for T (WH, p = 0.20; MD, p = 0.36), and T:C (WH, p = 0.94; MD, p = 0.63). Regarding the C, only the MD group showed increases (28%) after the matches (MD, p = 0.03; WH, p = 0.13). In conclusion MD group exacerbate the C response to friendly matches in elite young male soccer players, suggesting that dehydration before match may be an added stress to be considered.